Alasan Ketidaktepatan Waktu lbu untuk Melakukan lmunisasi Lengkap di Puskesmas Sawit Kabupaten Boyolali - Taufiqurrochman Nur Amin; Titik Kuntari (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2010)
The infant mortality rate in Indonesia is generally caused by the disease can be prevented by immunization (PD3I). In 2008 showed decreasing success rates of immunization. The complete success of immunization m Public Health Centers Sawit District Boyolali amounted 70-90%. This study aimed to identify factors that cause mothers to postpone the full immunization for children from birth through age 24 months. The study was non-analytic descriptive, using cross sectional method, the data used primary data obtained from questionnaires completed by respondents. Processed by descriptive statistics with proportion calculations and presented in tables and pie charts. Completed immunization showed number is 100% perfect. The timeliness of the implementation of immunization showed that the mother with right time just 30% while 70% delayed the immunization. The reasons of mother to delay immunization is because that their child had fever, coughing colds without fever, diarrhea, laziness mother to wait a long time, has other activity, and because the child exposed to DHF.